2019
DOI: 10.1177/0734016819846236
|View full text |Cite
|
Sign up to set email alerts
|

Police, Public, and Arrestee Perceptions of Body-Worn Video: A Single Jurisdictional Multiple-Perspective Analysis

Abstract: This article analyzes police, public, and arrestee survey responses from a single jurisdiction to give a multiple-perspective insight into the use of body-worn video (BWV) cameras by police. Police attitudinal data were collected from before ( n = 190), during ( n = 139), and at the conclusion ( n = 221) of a BWV implementation trial. Public attitudes were collected at the conclusion of the BWV implementation trial via online survey ( n = 995 respondents) and intercept survey ( n = 428 respondents). Arrestee a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…From the court perspective, there was limited indication that BWV evidence encouraged earlier guilty pleas, but no evidence that the rate of guilty pleas or convictions increased. Anecdotal evidence from officers involved in the trial may partially explain this, with a large majority indicating at the time of analysis very few of the incidents they had attended when using BWV had appeared in court, and when cases had appeared in court there was a feeling that the BWV footage was not readily accepted (Clare et al 2019). Furthermore, we note that this study was limited because not all of the cases were finalized at the time of the analysis.…”
Section: Discussionmentioning
confidence: 97%
“…From the court perspective, there was limited indication that BWV evidence encouraged earlier guilty pleas, but no evidence that the rate of guilty pleas or convictions increased. Anecdotal evidence from officers involved in the trial may partially explain this, with a large majority indicating at the time of analysis very few of the incidents they had attended when using BWV had appeared in court, and when cases had appeared in court there was a feeling that the BWV footage was not readily accepted (Clare et al 2019). Furthermore, we note that this study was limited because not all of the cases were finalized at the time of the analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of police attitudes in this area indicated that, while not particularly strong, respondents believed using a BWC would improve their personal safety (Gaub et al, 2016;Gramaglia and Phillips, 2018;Jennings et al, 2015;Wooditch et al, 2020). Officers in Western Australia questioned the ability of a BWC to increase their safety (Clare et al, 2019). These results suggest a reasonably soft relationship between the use of BWCs and increased feelings of safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A second subcategory focused on using BWCs for evidentiary purposes. Several studies reported that officers saw a BWC as tool to improve evidence collection and quality (Clare et al, 2019;Gaub et al, 2016;Goodall, 2007;Jennings et al, 2015;Pelfrey and Kenner, 2018;Smith, 2019;White et al, 2018). Police officers also felt a BWC could improve their recollection of incident events, reducing errors in their report writing (Jennings et al, 2015;Pelfrey and Kenner, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations